Proximate, Mineral and Fatty Acid Composition of Catla catla Reared in Fresh Water and Waste Water Environment - Paul, Baidya Nath; Mandal, Rathindra Nath; Chakrabarti, Partha Pratim; Adhikari, Subhendu; Pandey, Bijay Kumar; Singh, Puja; Bhowmick, Sadrupa (Indian Journal of Animal Nutrition, 2018)
The study was carried out to determine the differences in proximate, mineral and fatty acid composition of Catla catla reared in freshwater (FW) and wastewater (WW). The samples were collected from different places of West Bengal and the weight ranges from 250-2500g. Crude lipid, total ash and the moisture content did differ significantly between the two groups. However, protein content was significantly higher (P